Probing in vivo interactions between flavodiiron proteins and thioredoxins in Synechocystis sp. PCC 6803 - Vähäsarja, Janette (My University, 2022)
Synechocystis is a cyanobacterium that is capable of photosynthesis, and it can grow heterotrophically as well as phototrophically. Flavodiiron proteins are proteins that catalyze the Mehler-like reaction in photoreduction of oxygen into water. This works as an electron sink when light intensity suddenly increases or carbon assimilation is prohibited. Synechocystis has four different flavodiiron proteins that work as heterooligomers. Thioredoxins are enzymes that catalyze disulphide/dithiol exchange in order to adjust the activity of enzymes. Flavodiiron proteins have been found to have several conserved cysteine residues, which could work as targets for thioredoxin regulation. Synechocystis cells were transformed to produce fusion proteins of TrxA, Flv1, Flv2 and Flv3, where each protein was fused with one half of the yellow fluorescent protein Venus. By using bimolecular fluorescence complementation, it was possible to determine whether or not TrxA ever came close enough to one of the flavodiiron proteins for the Venus fragments to form a complete fluorescent protein. A successful completion of Venus would indicate that the two proteins in question interact with each other. TrxA was found to interact with Flv1 and Flv2, but not with Flv3. These interactions took place in the thylakoid membrane.
Keywords: Cyanobacteria, Synechocystis sp. PCC 6803, thioredoxin, TrxA, flavodiiron proteins, FDP